Autism and the Sensory Disruption of Social Experience - Boldsen, Sofie (Frontiers in Psychology, 2022)
Autism research has recently witnessed an embodied turn. In response to the cognitivist approaches dominating the field, phenomenological scholars have suggested a reconceptualization of autism as a disorder of embodied intersubjectivity. Part of this interest in autistic embodiment concerns the role of sensory differences, which have recently been added to the diagnostic criteria of autism. While research suggests that sensory differences are implicated in a wide array of autistic social difficulties, it has not yet been explored how sensory and social experience in autism relate on a phenomenological level. Given the importance of the sensory dimension of social encounters in phenomenological analyses of autism, this question must be considered crucial. This article investigates the role played by sensory differences in autistic social experience. Through a phenomenological analysis informed primarily by the philosophy of Maurice Merleau-Ponty with particular emphasis on the relation between intersubjectivity and perception, I argue that sensory differences affect the way other people appear in autistic experience on a pre-reflective level. By drawing on autistic young adults' experiential descriptions of social encounters, this article identifies three aspects of how sensory differences affect social experiences in autism. First, social encounters manifested as sensorially disturbing, chaotic, and unpredictable events. Second, the embodied expressions of others appeared unfamiliar, threatening, and promoted a sense of detachment from the social world. Third, deliberate practices were employed to actively seek out perceptual and social meaning in these disorienting social encounters. This analysis stresses the importance of understanding embodied intersubjectivity through its sensory dimensions. In addition, it indicates an important avenue for future research in exploring the potential role of practice in maintaining an intuitive grip on social meaning. By approaching social encounters as sensory and perceptual events, I emphasize how social difficulties in autism are inherently world-involving phenomena rather than a cognitive deficit reducible to the autistic person.